Impact of anaemia treatment for left ventricular remodelling prior to initiation of dialysis in chronic kidney disease patients: Efficacy and stability of long acting erythropoietin stimulating agents. (December 2015) - Io, Hiroaki; Aizawa, Masashi; Funabiki, Kazuhiko; Horikoshi, Satoshi; Tomino, Yasuhiko
Abstract: Aim: Anaemia is a common complication in patients with chronic kidney disease (CKD), which may initiate or accelerate left ventricular (LV) hypertrophy (LVH). The present study is a retrospective analysis to assess whether anaemia treatment is independently associated with LV remodelling prior to initiation of dialysis in CKD patients. Methods: Biochemical and physical values were collected over a period of more than 120 days prior to the initiation of dialysis in 27 patients with CKD. The left ventricular mass index (LVMI) was evaluated by echocardiography twice (at the baseline and the follow‐up at the initiation of the dialysis period). Results: Patients using long‐acting erythropoietin stimulating agents (L‐ESA) had the tendency of maintaining higher levels of haemoglobin (Hb) than those using short‐acting ESA (S‐ESA). Patients using L‐ESA showed a more significant improvement in the erythropoietin resistance index (ERI) than those of using S‐ESA. In a multivariate regression analysis, the average Hb level for the observational period, the level of Hb at the initiation of dialysis and the use of L‐ESA were independently associated factors for the LVMI at the initiation of dialysis. A lower LVMI at the initiation of dialysis and an improvement of the LVMI during the observational period were detected in the highest tertile of average Hb (10.4 g/dL). Conclusion: Long‐acting ESA was effective and stable when treating anaemia until the start of dialysis. It is important to treat anaemia for the prevention of LV remodelling in CKD patients. These findings have some therapeutic implications for treatment strategies for pre‐dialysis patients.